2013
DOI: 10.3379/msjmag.1310r002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Flat FePd-Alloy Epitaxial Thin Film with L10 Ordered Structure by Low-Temperature Deposition Followed by Annealing

Abstract: FePd-alloy thin films of 40 nm thickness are prepared on MgO single-crystal substrates of (001), (110), and (111) orientations by employing a two-step method consisting of deposition at a low temperature of 200 °C followed by annealing at a higher temperature in a range from 300 to 600 °C. The influences of substrate orientation and annealing temperature on the ordered phase formation and the surface roughness are investigated. FePd films with disordered A1 structure grow epitaxially on MgO substrates of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Films without annealing were also prepared. The details of film preparation were similar to our previous studies [8], [9]. The surface morphology was observed by atomic force microscopy (AFM).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Films without annealing were also prepared. The details of film preparation were similar to our previous studies [8], [9]. The surface morphology was observed by atomic force microscopy (AFM).…”
Section: Methodsmentioning
confidence: 98%
“…In our previous studies [8], [9], FePd films of 40 nm thickness were prepared on MgO(001) substrates by two different methods. One was a one-step method consisting of high-temperature deposition at 600 °C, where L1 0 crystals nucleated on the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the film morphology is influenced during the film deposition process, a two-step process technique consisting of a low temperature film deposition followed by a high temperature annealing for L10 ordering has been investigated to prepare an L10 ordered film with improved surface flatness 153,174,175,177) . Figure 20 compares the surface structures of FePd thin films of 2 -40 nm thicknesses observed by atomic force microscopy (AFM).…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] The authors have shown that a twostep process consisting of low temperature film formation followed by high temperature annealing is effective for the preparation of L1 0 -FePt thin film with an improved surface flatness. 6,7 When an Fe-Pt alloy thin film is formed on an oxide substrate such as MgO(001) single-crystal at low temperatures where the impinging atom migration is limited, the film morphology tends to be continuous with small surface undulations. By heating the film at a higher temperature, migration of atoms within the film proceeds to form an L1 0 -ordered structure keeping the film morphology.…”
Section: Introductionmentioning
confidence: 99%